Lysines in the tetramerization domain of p53 selectively modulate G1 arrest. Issue 11 (2nd June 2016) - Beckerman, Rachel; Yoh, Kathryn; Mattia-Sansobrino, Melissa; Zupnick, Andrew; Laptenko, Oleg; Karni-Schmidt, Orit; Ahn, Jinwoo; Byeon, In-Ja; Keezer, Susan; Prives, Carol
ABSTRACT: Functional in a tetrameric state, the protein product of the p53 tumor suppressor gene confers its tumor-suppressive activity by transactivating genes which promote cell-cycle arrest, senescence, or programmed cell death. How p53 distinguishes between these divergent outcomes is still a matter of considerable interest. Here we discuss the impact of 2 mutations in the tetramerization domain that confer unique properties onto p53. By changing lysines 351 and 357 to arginine, thereby blocking all post-translational modifications of these residues, DNA binding and transcriptional regulation by p53 remain virtually unchanged. On the other hand, by changing these lysines to glutamine (2KQ-p53), thereby neutralizing their positive charge and potentially mimicking acetylation, p53 is impaired in the induction of cell cycle arrest and yet can still effectively induce cell death. Surprisingly, when 2KQ-p53 is expressed at high levels in H1299 cells, it can bind to and transactivate numerous p53 target genes including p21, but not others such as miR-34a and cyclin G1 to the same extent as wild-type p53. Our findings show that strong induction of p21 is not sufficient to block H1299 cells in G1, and imply that modification of one or both of the lysines within the tetramerization domain may serve as a mechanism to shunt p53 from inducing cell cycle arrest.